The potential intersections of COVID-19, gender and food security in Africa - Doss, Cheryl R.; Njuki, Jemimah; Mika, Helena (2020)
Many responses to Covid-19, both in policy and analysis, fail to consider how gender interacts with implemented measures and their implications for food security in Africa. An understanding of these potential intersections is, however, crucial for a gender-sensitive response that ensures both women’s own food security and their ability to safely perform crucial roles in the food value chain. We draw on evidence from past health crises, reports from the Covid-19 pandemic, and literature on gender and food security, to draw out potential gendered effects across four nodes: production, processing, trading, and consumption. We analyze how gendered structures can lead to an increase in women’s care work, an increase in women’s agricultural work in substitution for import-restricted inputs, a disproportionate financial effect due to women’s prevalence in local markets and street vendor sectors, and consequent health effects due to women’s central role in food preparation and household nutrition.